Exploration Of Organizational Culture And Compensation Factors In Enhancing Employee Performance - Budiman, Budiman (Sean Institute, 2025)
This study examines the impact of organizational culture and compensation on employee performance at PT XYZ. A strong organizational culture and fair compensation system are recognized as key drivers for enhancing employee performance and overall company productivity. Using a quantitative approach, data were collected via questionnaires distributed to 50 respondents, and multiple linear regression analysis was employed to explore the effects of these variables. The analysis reveals that organizational culture has a significant partial effect on employee performance, supporting the acceptance of the alternative hypothesis. Conversely, compensation does not exhibit a significant partial effect, leading to the acceptance of the null hypothesis. However, when analyzed simultaneously, organizational culture and compensation collectively have a significant effect on employee performance. The coefficient of determination shows that just over half of the variation in employee performance is explained by organizational culture and compensation, while the remainder is influenced by other factors not examined in this study. The findings suggest that enhancing a positive organizational culture should be prioritized as a primary strategy for improving employee performance at PT XYZ, as it plays a more critical role than compensation in driving results.